A trajetória escolar e social de jovens atendidos por organizações da sociedade civil: ensino superior e ações afirmativas - Sayar, Karoline Rezende (2018)
The theme of this dissertation refers to the school and social trajectories of young people attended by Civil Society Organizations. To allow a better understanding of the theme, some works by Bourdieu and Lahire that discuss cultural capital, social capital, habitus and cursus will be used as a theoretical reference. The subjects of study of the research are young people attended by the organization Cidadão Pro Mundo, whose objective is the teaching of the English language, aged between 17 and 25 years, and who are not attending higher education. The paper aimed to answer the question: what are the structuring factors in the trajectory of young people attended by the NGO Cidadão Pró Mundo regarding their fate in higher education? For this, the research applied questionnaires and interviewed some young people from the NGO Cidadão Pró Mundo. All the young people who participated in the research wish to attend higher education, and seek a higher education than their parents, their strategies are based on habitus, understood as durable dispositions structured according to the social environment of the agent that would serve as structuring structures of the practices. It is possible to highlight: the young people are aware of the difficulties of reaching vacancies in public or private higher education with scholarship, so they started to adopt strategies that structure their trajectories, such strategies are: mastery of a second language, participation in civil society organizations for job placement, and looking for an international career